WYBÓR I OBJĘCIE URZĘDU PRZEZ CENZORÓW W STAROŻYTNYM RZYMIE - Tarwacka, Anna (Zeszyty Prawnicze, 2016)
Elections and Entrance in Office by Censors in the Roman Republic Summary Censors were major magistrates usually elected every five years for eighteen months. Their elections were held by one of the consuls at the comitia centuriata during which both censors had to get chosen. It was obligatory to postpone the assembly in case only one candidate achieved the majority of votes. After the election had been completed, another comitia centuriata were held in order to vote a lex centuriata confirming it. Only then the censors enetred in office. If during the term of office one of the censors died, the other one was obliged to resign. The office was reserved for patricians until 351 B.C. whereas since 339 B.C. according to the lex Publilia Philonis both censors could be plebeians. The rule considering iteratio impossible in case of censorship was confirmed in a law voted around 265 B.C. The first task awaiting newly elected censors was to contract for the food of the sacred geese and renovation of Juppiter statue.